Usia dengan Kejadian Anemia dan Defisiensi Zat Besi pada Ibu Hamil - Sri Yunida; Rostika Flora; Rico J. Sitorus; Indah Yuliana; Nurlaili Nurlaili (Journal of Telenursing (JOTING), 2022)
This study aims to describe the iron profile of pregnant women at risky ages in the Kepahiang District. The method used is descriptive-analytic with a cross-sectional design. The research sample was 100 pregnant women in the second and third trimesters randomly from 14 working areas of the Public Health Center in Kepahiang Regency. Determination of anemia and iron deficiency status is carried out based on blood sampling to measure hemoglobin levels and serum iron levels. The results showed that most of the respondents (55%) were at risky age and almost all (75%) had anemia and as many as 51 respondents had iron deficiency. The bivariate analysis results obtained a value of p = 0.049 and PR = 2.820 for the relationship between age and the incidence of anemia and p = 0.003 and PR = 3.789 for the relationship between age and the incidence of iron deficiency. In conclusion, there is a significant relationship between age and the incidence of anemia and between age and iron deficiency in pregnant women in Kepahiang Regency. Keywords: Anemia, Deficiency, Pregnant Women, Age, Iron